High and reversible lithium ion storage in self-exfoliated triazole-triformyl phloroglucinol-basedcovalent organic nanosheets - Haldar, Sattwick; Roy, Kingshuk; Nandi, Shyamapada; Chakraborty, Debanjan; Puthusseri, Dhanya; Gawli, Yogesh; Ogale, Satishchandra; Vaidhyanathan, Ramanathan (Advanced Energy Materials, 2018)
Covalent organic framework (COF) can grow into self-exfoliated nanosheets. Their graphene/graphite resembling microtexture and nanostructure suits electrochemical applications. Here, covalent organic nanosheets (CON) with nanopores lined with triazole and phloroglucinol units, neither of which binds lithium strongly, and its potential as an anode in Li-ion battery are presented. Their fibrous texture enables facile amalgamation as a coin-cell anode, which exhibits exceptionally high specific capacity of approximate to 720 mA h g(-1) (@100 mA g(-1)). Its capacity is retained even after 1000 cycles. Increasing the current density from 100 mA g(-1) to 1 A g(-1) causes the specific capacity to drop only by 20%, which is the lowest among all high-performing anodic COFs. The majority of the lithium insertion follows an ultrafast diffusion-controlled intercalation (diffusion coefficient, D-Li(+) = 5.48 x 10(-11) cm(2) s(-1)). The absence of strong Li-framework bonds in the density functional theory (DFT) optimized structure supports this reversible intercalation. The discrete monomer of the CON shows a specific capacity of only 140 mA h g(-1) @50 mA g(-1) and no sign of lithium intercalation reveals the crucial role played by the polymeric structure of the CON in this intercalation-assisted conductivity. The potentials mapped using DFT suggest a substantial electronic driving-force for the lithium intercalation. The findings underscore the potential of the designer CON as anode material for Li-ion batteries.

Hydroxide ion-conducting viologen-bakelite organic frameworks for flexible solid-state zinc-air battery applications - Rase, Deepak; Illathvalappil, Rajith; Singh, Himan Dev; Shekhar, Pragalbh; Leo, Liya S.; Chakraborty, Debanjan; Haldar, Sattwick; Shelke, Ankita; Ajithkumar, Thalasseril G.; Vaidhyanathan, Ramanathan (Nanoscale Horizons, 2023)
Adaptable polymer-based solid-state electrolytes can be a game-changer toward safe, lightweight flexible batteries. We present a robust Bakelite-type organic polymer covalently decked with viologen, triazine, and phenolic moieties. Its flexible structure with cationic viologen centers incorporates counter-balancing free hydroxide ions into the polymeric framework. By design, the aromatic groups and heteroatoms in the framework can be activated under an applied potential to prompt a push-pull drive, setting off the towing of hydroxide ions via weak electrostatic, van der Waals, and hydrogen-bond interactions. The frontier orbitals from a DFT-modeled structure certify this. The hydroxyl-polymer requires minimal KOH wetting to maintain a humid environment for Grotthuss-type transport. The hydroxide ion conductivity reaches a value of 1.4 x 10(-2) S cm(-1) at 80 degrees C and 95% RH, which is retained for over 15 h. We enhanced its practical utility by coating it as a thin solid-state separator-cum-electrolyte on readily available filter paper. The composite exhibits a conductivity of 4.5 x 10(-3) S cm(-1) at 80 degrees C and 95% RH. A zinc-air battery (ZAB) constructed using this polymer-coated paper as electrolyte yields a maximum power density of 115 mW cm(-2) and high specific capacitance of 435 mA h g(-1). The power density recorded for our ZAB is among the best reported for polymer electrolyte-based batteries. Subsequently, the flexible battery fabricated with IISERP-POF11_OH@FilterPaper exhibits an OCV of 1.44 V, and three batteries in series power a demo traffic signal. To underscore the efficiency of hydroxide ion transport through the complex multifunctional backbone of the polymer, we calculated the diffusion coefficient for OH- (Exp: 2.9 x 10(-5) cm(2) s(-1); Comp. 5.2 x 10(-6) cm(2) s(-1)) using electrochemical methods and MD simulations. Climbing-edge NEB calculations reveal a large energy barrier of 2.11 eV for Zn2+ to penetrate the polymer and identify hydroxide ions within the polymer, suggesting no undesirable Zn2+ crossover. Our findings assert the readily accessible C-C-linked cationic polymer's capacity as a solid-state electrolyte for ZABs and any anion-conducting membrane.